Development booklet 3-dimensional image-based digital as learning media on virus materials for senior high school - Sakinah, Shalmita; Arsih, Fitri; Syamsurizal, Syamsurizal; Rahmatika, Helsa (JPBIO (Jurnal Pendidikan Biologi), 2024)
Learning media is something that is used to increase student’s interest in learning activities. Limited learning media makes biology material difficult for students to understand. Virus material is a type of biological material that has a lot of material and images that are difficult to understand. So, learning media needed that is concise and has attractive images in the form of booklet 3-dimensional image-based digital as a learning medium for viral material for Senior High School. This research aims to test the feasibility and practicality booklet 3-dimensional image-based digital as a learning medium for virus material at Kartika High School 1-5 Padang. This research is a development using Thiagarajan's 4-D development model. Based on the research results obtained as follows: material expert validation results 90.15% in the very good category, media experts 94.69% in the very good category, teacher practicality test results 95.83% in the very good category, student practicality test 89.10% in the very good category. Can be concluded that booklet digital material developed on viral material is feasible and capable of increasing student interest..